Key factors in the reform of competence-based science teaching in Spain. A case study with secondary school teachers involved in a training programme focusing on context-based approach - Lupión-Cobos, Teresa; Hierrezuelo-Osorio, José Manuel; Cruz-Lorite, Isabel; Blanco-López, Ángel (Taylor & Francis, 2022)
Background: Numerous investigations have highlighted the importance of examining teachers' responses to the curricular reforms in science teaching proposed by the educational authorities. Science teachers' responses are shaped by their perceptions of the new measures' intentions and their level of involvement. Purpose: This study analyses the evolution of the teachers´ beliefs and opinions to externally driven curriculum reform in Spain focused on developing key competences. Sample: Four secondary science teachers participated in a training programme in which a context-based approach to teaching scientific competences was implemented. Design and Methods: The data analysis applied the scheme proposed by Ryder (2015), referring to the personal, internal and external focus of teachers' work. It also introduced the qualifier concept, whether their responses were seen as facilitating (F) or obstacles (O) the development of competence-based science education. The data was obtained from different settings: two individual interviews with each teacher and a focus group carried out with the four teachers Results: The teachers’ perceptions cover many aspects (20), which could all be categorized in the 27 factors included in Ryder’s scheme (2015). The teachers’ perceptions were mainly on the personal focus at all training programme settings. However, their responses also reflected factors related to the internal and external focuses, though to a lesser extent. Conclusion: The study´s findings show the influence of reflection on the teachers’ observations and impressions, helping them elicit many factors according to Ryder´s proposal. As for the qualifiers expressed by the teachers, the evaluations depended on the teacher profile and the settings used. These considerations highlight the influence of training and experiential knowledge on professional development.
Keywords: Cambio curricular; Enseñanza secundaria; Profesores; Ciencias naturales; Science curriculum reforms; Context-based teaching; Teachers’ response; Teachers’ reflection